IDEAS OF CHARACTER EDUCATION AT THE INTEGRATED ISLAMIC ELEMENTARY SCHOOL IN BANJARMASIN - Galuh Nashrulloh Kartika Majangsari Rofa (Ri'ayah: Jurnal Sosial dan Keagamaan, 2019)
Character problems are increasingly diverse that is evidenced by the increasing violence and criminal acts on children, pornography, drug abuse and other deviant acts. Integrated Islamic Primary School as one of the three types of elementary school institutions is expected to an alternative solution. This research focused on the analysis of ideas on character education at an Integrated Islamic Elementary School. This qualitative field research employed a phenomenological approach. The data were collected from the documents at the school, interview with the founders, and observation to triangulate the data. This research argued that the idea was to answer the needs of the local community, especially the upper middle class. The main purpose of education is to develop the potential of students' nature towards creating a generation with courageous and character leaders based on the Koran and the Sunnah. The 7 characters were instilled as a hallmark of character education at the school. These characters are adopted from Hassan Al-Banna's thought in "Tarbiyah's mission." This point confirmed Hasan’s contention. However, there is a slight difference in terms of nationalism, namely that the school run a 5 pillar government program on character education (PPK) in implementing the school's vision and mission.